2004
DOI: 10.1159/000075925
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Lipid Metabolism and the Role of Lipids in Progressive Renal Disease

Abstract: Dyslipidemia contributes to the rate of progression of atherosclerosis and chronic kidney disease. Also, chronic kidney disease leads to the development of secondary abnormalities in lipid metabolism that contribute to increased cardiovascular morbidity and mortality. This review presents the mechanisms that underlie this risk. The mechanisms of normal cellular lipid metabolism and the abnormalities that develop in association with inflammation are reviewed. There is a special emphasis on foam cells in the kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
187
1
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(200 citation statements)
references
References 41 publications
(59 reference statements)
7
187
1
5
Order By: Relevance
“…The SREBP-2 isoform activates genes of the cholesterogenic pathway, whereas the two SREBP-1 isoforms are more active in regulating the synthesis of fatty acids. [43][44][45][46] In the current study, the slightly lower hepatic expression of PPARa in db/db than m/m mice was significantly increased by morroniside treatment (Fig. 5A).…”
Section: Discussionmentioning
confidence: 64%
“…The SREBP-2 isoform activates genes of the cholesterogenic pathway, whereas the two SREBP-1 isoforms are more active in regulating the synthesis of fatty acids. [43][44][45][46] In the current study, the slightly lower hepatic expression of PPARa in db/db than m/m mice was significantly increased by morroniside treatment (Fig. 5A).…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, the presence of dyslipidemia in these patients might enhance the rate of decline in renal function and chronic kidney disease (CKD) progression, generally by raising the inflammation and the oxidative stress in the renal microenvironment [143][144][145][146]. In the post-hoc analyses of randomized controlled trials (RCTs) the benefits of statins in myocardial infarction (MI) also extend to patients with mild-to-moderate renal insufficiency [147], but these patients are more prone to CVD than progress to end-stage kidney disease [147].…”
Section: Kidney Diseases and Statin Intolerancementioning
confidence: 99%
“…They are directly exposed to lipoproteins in pathological states like in nephrotic syndrome and can uptake lipids via its scavenger receptors 3, 4. Evidence has shown that hypercholesterolaemia at early stage may aggravate renal injury primarily via podocytes rather than other residential cells and forced podocyte injury could secondarily lead to mesangial sclerosis 5, 6, 7. Therefore, further understanding of mechanisms of hypercholesterolaemia‐associated podocyte injury is of great importance.…”
Section: Introductionmentioning
confidence: 99%